MADRS single items differential changes among patients with melancholic and unspecified depression treated with ECT: an exploratory study - Pozuelo Moyano, Beatriz; Ranjbar, Setareh; Swierkosz-Lenart, Kevin; Schuster, Jean Pierre; Zullo, Leonardo; von Gunten, Armin; Vandel, Pierre (Frontiers in Psychiatry, 2024)
IntroductionMajor depressive disorder (MDD) exhibits heterogeneity in treatment response.ObjectiveThis exploratory analysis aims to evaluate the differential changes in individual items of the MADRS between melancholic MDD (M-MDD) and unspecified MDD (U-MDD) following electroconvulsive therapy (ECT).MethodsThe study included 23 patients with unipolar MDD who received ECT. Patients were classified as M-MDD or U-MDD according to DSM-5 criteria. MADRS scores were assessed at baseline and one-month post-ECT. Differences between subtypes were analyzed using the Wilcoxon test and multiple linear regression.ResultsAmong 23 participants receiving ECT for MDD, 10 had M-MDD and 13 had U-MDD. Baseline MADRS items showed significantly higher scores in the M-MDD group, except for reported sadness, suicidal ideation, and concentration difficulties. Total MADRS score reduction was significantly greater in the M-MDD group. This decline was especially pronounced in M-MDD patients for specific items, including apparent sadness, inability to feel, pessimistic thoughts, sleep disturbances, reduced appetite, and concentration difficulties, after adjusting for age and sex.ConclusionMADRS score reductions were more substantial for M-MDD than U-MDD in both total and specific items following one month of ECT. Further research with larger samples is needed to clarify MADRS response differences after ECT between melancholic and unspecified depressive subtypes.